2018
DOI: 10.21873/anticanres.12695
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Prognostic Impact of VEGF, CD31 and αSMA in Resected Primary Lung Cancers

Abstract: Not the number of tumor vessels but their maturation may be a prognostic factor of patients with lung cancer. VEGF may not only stimulate proliferation of endothelial cells but also their maturation in differentiated lung cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…This result is in keeping with that reported by El-Gohary et al in prostatic adenocarcinoma tissues [45]. However, several other studies on different types of cancer showed no association between the two proteins [8,35,46,47]. Our result indicates a possible contribution of VEGF-A in microvessel formation, but further studies with larger sample size are required to determine the type of the relationship between VEGF-A and CD31 in NSCLC in order to have a clearer insight into the related angiogenesis pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in keeping with that reported by El-Gohary et al in prostatic adenocarcinoma tissues [45]. However, several other studies on different types of cancer showed no association between the two proteins [8,35,46,47]. Our result indicates a possible contribution of VEGF-A in microvessel formation, but further studies with larger sample size are required to determine the type of the relationship between VEGF-A and CD31 in NSCLC in order to have a clearer insight into the related angiogenesis pathway.…”
Section: Discussionsupporting
confidence: 92%
“…Our statistical analysis showed higher staining scores of VEGF-A, CD31 and GRP78 in adenocarcinoma compared with squamous cell carcinoma (p-value < 0.001, p-value = 0.001, and p-value = 0.045, respectively). The positive correlation between VEGF-A expression and adenocarcinoma was previously revealed in many studies [32][33][34][35]. On the other hand, other researchers could not come out with the same conclusion neither for CD31 [8,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 88%
“…VEGF, a powerful angiogenic agent in neoplastic tissues, has been widely studied in the field of neoplastic vascularization (14). Previous researches had confirmed the expression of VEGF was increased in many cancers, including colon cancer (15), lung cancer (16), breast cancer (17), and gastric cancer (18), which indicated the poor survival for patients. Bevacizumab, a recombinant humanized monoclonal antibody to VEGF and known by its brand name, Avastin®, blocks tumor cell-derived VEGF-A, impairing the development of new vessels and leading to tumor starvation and, consequently, growth inhibition (19).…”
Section: Discussionmentioning
confidence: 96%
“…As a marker of angiogenesis, these findings potentially show the presence of increased angiogenesis within the Bladder tumours. The scoring system used in this research examines both staining intensity and percentage positivity in tumour cells and has been used by others [27].…”
Section: Discussionmentioning
confidence: 99%